# Algebra

Solo disponible en BuenasTareas
• Páginas : 2 (400 palabras )
• Descarga(s) : 0
• Publicado : 10 de septiembre de 2012

Vista previa del texto
1.-(5+4i) + (7+6i) = 5+4i+7+6i= 5+7+4i+6i= (5+7) + (4+6) i=12+10i

2.-(20+6i) + (10+4i) = 20+6i+10+4i= 20+10+6i+4i= (20+10) + (6+4) i=30+10i3.-(6+3i) + (9+5i) = 6+3i+9+5i= 6+9+3i+5i= (6+9) + (3+5) i=15+8i

4.-(2+7i) + (8+8i) = 2+7i+8+8i= 2+8+7i+8i= (2+8) + (7+8) i=10+15i5.-(6+8i) + (7+9i) = 6+8i+7+9i= 6+7+8i+9i= (6+7) + (8+9) i=13+17i

6.-(3+2i) + (5+2i) = 3+2i+5+2i= 3+5+2i+2i= (3+5) + (2+2) i=8+4i

7.-(4+2i)+ (3+4i) = 4+2i+3+4i= 4+3+2i+4i= (4+3) + (2+4) i=7+6i

8.-(11+6i) + (9+7i) = 11+6i+9+7i= 11+9+6i+7i= (11+9) + (6+7) i=20+13i

9.-(21+4i) +(8+6i) = 21+4i+8+6i= 21+8+4i+6i= (21+8) + (4+6) i=29+10i

10.-(8+8i) + (9+8i) = 8+8i+9+8i= 8+9+8i+8i= (8+9) + (8+8) i=17+16i

11.-(7+7i) +(7+8i) = 7+7i+7+8i= 7+7+7i+8i= (7+7) + (7+8) i=14+15i

12.-(2+5i) + (6+12i) = 2+5i+6+12i= 2+6+5i+12i= (2+6) + (5+12) i=8+17i

13.-(9+3i) +(6+7i) = +9+3i+6+7i= 9+6+3i+7i= (9+6) + (3+7) i=15+10i

14.-(3+9i) + (0+4i) = 3+9i+0+4i= 3+0+9i+4i= (3+0) + (9+4) i=3+13i

15.-(15+5i) +(10+5i) = 15+5i+10+5i= 15+10+5i+5i= (15+10) + (5+5) i=25+10i

16.-(18+7i) + (8+15i) = 18+ 7i+8+15i= 18+8+7i+15i= (18+8) + (7+15) i=26+22i17.-(5+9i) + (9+8i) = 5+9i+9+8i= 5+9+9i+8i= (5+9) + (9+8) i=14+17i

18.-(4+7i) + (1+2i) = 4+7i+1+2i= 4+1+7i+2i= (4+1) + (7+2) i=5+9i19.-(13+5i) + (9+12i) = 13+5i+9+12i= 13+9+5i+12i= (13+9) + (5+12) i=22+17i

20.-(8+7i) + (7+9i) = 8+7i+7+9i= 8+7+7i+9i= (8+7) + (7+9) i=15+16i